Penatalaksanaan Fisioterapi Pada Kasus Osteoarthritis Lutut Bilateral Di Rsud Dr. Soehadi Prijonegoro - Pingita Nadia Khulsum, Dela, Maskun Pudjianto (2016)
Background : Osteoarthritis is a progressive disease that illustrates the failure of repair joint damage, this situation is trggered by abnormal stress on intra- articular, painful as the main factors causing the problem limited mobility, decreased muscle, muscle spasm until decrease functional activity. Objective : To find out the benefits of the use of Infra Red (IR), Transcutaneus Electrical Nerve Stimulation (TENS), and quadriceps bench exercise in the case of osteoarthritis knee bilateral. Result : After treatment for 6 times found a decrease in the degree of pain silent T1 : 2 to T6 : 1, tenderness T1 : 6 to T6 : 3, and pain motion T1 : 6 to T6 : 3, an increased range of motion (LGS) in knee dextra joint active movement T1 : S : 0º-0º-125º to T6 : S : 0º-0º-140º, knee dextra joint pasive movement T1 : S : 0º-0º-140º to T6 : S : 0º-0º-142º, knee sinistra joint active movement T1 : S : 0º-0º-130º to T6 : S : 0º-0º-138º, knee sinistra joint pasive movement T1 : S : 0º-0º-140º to T6 : S : 0º-0º-145º, an increased muscle strengthening of m. hamstring dextra T1 : 3- to T6 : 4, m. hamstring sinistra T1 : 3- to T6 : 5, m. quadricpes dextra T1 : 4 to T6 : 5, m. quadriceps sinistra T1 : 4 to T6 : 5, and an increased functinal activity of knee T1 : 34 to T6 : 18. Conclution : After granting modalities Infra Red (IR), Transcutaneus Electrical Nerve Stimulation (TENS), and quadriceps bench exercise in the case of osteoarthritis knee bilateral can reduce the degree of pain, increased range of motion (LGS), increased muscle strengthening, and enhance the functional activity of the knee joint.